Another Life - Joseph-Vilain, Mélanie; Misrahi-Barak, Judith (Horizons anglophones, 2012)
Many writers started their professional lives in very diverse fields before embracing writing, or on the contrary have turned away from writing. The present volume seeks to explore the complex relationship between that 'other life' and writing. The aim is to determine whether a writer's 'other life' appears in, influences or even shapes his/her work, and to what extent. What is the part of gestation and that of rupture? A diversity of writers is examined: Patrick Chamoiseau, J. M. Coetzee, Jan J. Dominique, Janet Frame, Amitav Ghosh, L. K. Johnson, Wilson Harris, Dany Laferrière, Yannick Lahens, NourbeSe Philip, Emmelie Prophète, Arundhati Roy, Edward Said, but also Bartolomé de las Casas and E. L. Grant Watson. Unpublished autobiographical essays and a poem are included, especially written for the volume by Marie-Célie Agnant, Cyril Dabydeen and Fred D'Aguiar.